European Elections in Croatia - Cipek, Tihomir (Political Preferences, 2014)
This text discusses the results of European elections in Croatia. It reaches the conclusion that voters, unhappy with the economic situation, punished the ruling social democratic coalition which suffered a heavy defeat. On the other hand, election results prove the recovery of HDZ, the opposition, centre-right party. It is also obvious that most Croatian citizens do not believe that European elections are important enough to warrant voting. Euroscepticism in Croatia is on the rise because citizens see no obvious benefits from joining the European Union. On the contrary, it is becoming increasingly clear that, in its first year as a member, Croatia will pay more funds into EU budget than it will receive from it. It is evident that direct elections of European Parliament members did not succeed in strengthening EU's legitimacy in the eyes of Croatian voters, and that European elections are actually of secondary importance. Key words: European elections, Croatia, European Union, Euroscepticism